Collaborative Governance Bhabinkamtibmas dengan FKPM untuk Meningkatkan Keamanan dan Ketertiban di Kabupaten Puncak Jaya - Sipahutar, Hendrik R.; Silo, Akbar; Muhdiarta, Untung; Aedah, Nur (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2022)
This study aims to analyze the collaborative practice of Bhayangkara Pembina Security and Public Order (Bhabinkamtibmas) with the Community Policing Partnership Forum (FKPM) to improve public safety and security in Puncak Jaya Regency. The research method used is descriptive qualitative. The research location is in Puncak Jaya Regency. The technique of determining the information selected by snowball by assigning 2 people as informants. Data collection used in in-depth interviews and observations. Data analysis techniques include data reduction, data presentation, data interpretation and drawing conclusions. The results of the study indicate that Collaborative Governance is practiced by building synergies between government and non-government parties based on the Directives and Regional Regulations as a road map for creating social improvement. The design of community creation and security is inclusive and open with face-to-face dialogue and intensive outreach. The strategy developed is to increase the trust of the community to be able to cooperate with the security forces, by developing collaborative activities, mentoring and informal education to foster communities to carry out activities that build and improve their standard of living so as to avoid actions that can harm others.